Magnetoactive Acoustic Topological Transistors. Issue 18 (25th April 2022) - Lee, Kyung Hoon; Al Ba'ba'a, Hasan; Yu, Kunhao; Li, Ketian; Zhang, Yanchu; Du, Haixu; Masri, Sami F.; Wang, Qiming
Abstract: Topological field‐effect transistor is a revolutionary concept that physical fields are used to switch on and off quantum topological states of the condensed matter. Although this emerging concept has been explored in electronics, how to realize it in the acoustic realm remains elusive. In this work, a class of magnetoactive acoustic topological transistors capable of on‐demand switching on and off topological states and reconfiguring topological edges with external magnetic fields is presented. The key mechanism is to harness magnetic fields to tune air‐cavity volumes within acoustic chambers, thus breaking or preserving the inversion symmetry to manifest or conceal the quantum valley Hall effect. To switch the topological transport beyond the in‐plane routes, a magneto‐tuned non‐topological band gap to allow or forbid the wave transport out‐of‐plane is harnessed. With the reversible magnetic control, on‐demand switching of topological routes to realize topological field‐effect waveguides and wave regulators is demonstrated. Analogous to the impact of semiconductor transistors on modern electronics, this work may expand the scope of topological acoustics by achieving unprecedented functions in acoustic modulation. Abstract : Although topological field‐effect transistor has been explored in electronics, how to realize it in acoustics remains elusive. This study presents a class of magnetoactive acoustic topological transistors capable of on‐demand switching on and off topological states with external magnetic fields. Integrating magneto‐tunable topological and non‐topological band gaps, in‐plane and out‐of‐plane conductive routes can be on‐demand reconfigured without rebuilding structures.